Pemahaman Konsep Kehidupan Sosial Budaya Negara Anggota Asean dengan Pembelajaran Berbasis Multikultural di Kelas VI SDN Bendogerit 2 Kota Blitar - Ericca Retna Kusumswati (IJoIS: Indonesian Journal of Islamic Studies, 2022)
Social Sciences (IPS) is one of the subjects starting from SD/MI to university. In the future, students will face challenges because the life of the global community is changing all the time. Therefore, Social Sciences (IPS) is designed to develop knowledge, understanding, and analytical skills on the social conditions of society in entering a dynamic society. Especially learning in Class VI about the socio-cultural life of ASEAN Member States which was carried out at SDN Bendogerit 2, Sananwetan District, Blitar City. The results of learning in social studies learning can be said that the teacher is not successful, as shown by the data, namely from 29 students who achieved completeness as many as 9 students or 31%. Therefore, the teacher conducts research, while the research is used qualitatively on students in social studies learning. The type of research used is Classroom Action Research (CAR). Data analysis techniques used are data reduction, data presentation, and drawing conclusions. The learning facilities used are multicultural-based learning.